Association of Interleukin-10 Promoter Polymorphism (-1082 G/A) and Gastric Cancer in Andhra Pradesh Population of South India - Chand-Bhayal, Amar (Iran J Cancer Prev, 2012)
BACKGROUND: Gastric Cancer (GC) is one of the most commonly diagnosed malignancies. Genetic variation in genes encoding cytokines and their receptors, determine the intensity of the inflammatory response, which may contribute to individual differences in the outcome and severity of the disease. Interleukin-10 (IL-10) is a multifunctional cytokine with both immunosuppressive and antiangiogenic functions. Polymorphisms in the IL-10 gene promoter genetically determine inter-individual differences in IL-10 production. In the present study, we investigated the association between the IL-10 -1082 G/A polymorphism and the susceptibility to gastric cancer in a South Indian population from Andhra Pradesh. METHODS: We genotyped 100 patients diagnosed with gastric cancer and 132 healthy control subjects for -1082G/A single nucleotide polymorphism by Amplification Refractory Mutation System-Polymerase Chain Reaction (ARMS-PCR) method followed by agarose gel electrophoresis. RESULTS: The distribution of IL-10 genotypes at -1082 G/A were GG 18 %, GA 35% and AA 47 % in gastric cancer patients and GG 31.82 %, GA 37.88 % and AA 30.3% in control subjects. The allelic frequencies of G and A were 0.355 and 0.645 in GC patients and 0.508 and 0.492 in control subjects respectively. The IL-10 -1082 A allele was associated with risk of gastric cancer (OR=1.873, 95%CI-1.285-2.73and P= 0.001048**). CONCLUSION: Our study indicates that allele A of IL-10-1082 G/A polymorphism may be considered as one of the important risk factor in the etiology of gastric cancer.